Strain-enabled phase transition of periodic metasurfaces - Yu, Jiancan (2022)
Phase transitions are universal in solid-state matters, as well as in periodic electromagnetic metasurfaces-the photonic analogues of crystals. Although such transitions dictate the properties of active metasurfaces, universal ways to describe the structure transition of periodic metasurfaces have not yet been established. Here, the authors report the strain-enabled phase transition (or lattice deformation) of stretchable metasurfaces with the crystallographic description. They analytically and experimentally demonstrate the phase transition of plasmonic lattices between two arbitrary 2D Bravais lattices under certain strain configurations. The strain-induced symmetry lowering of the structures gives rise to optical anisotropy upon polarization, namely, linearly and circularly polarized dichroism. They further demonstrate the potential of phase transition in information decoding with applied strain. Interpreting the phase transition of metasurfaces from a standpoint of symmetry would accelerate the discovery of emergent properties, and provide a generalizable approach to designing active metasurfaces.